2009
DOI: 10.1007/s00449-009-0313-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling and analyses of simultaneous saccharification and fermentation process to produce bio-ethanol from rice straw

Abstract: The rice straw, an agricultural waste from Asians' main provision, was collected as feedstock to convert cellulose into ethanol through the enzymatic hydrolysis and followed by the fermentation process. When the two process steps are performed sequentially, it is referred to as separate hydrolysis and fermentation (SHF). The steps can also be performed simultaneously, i.e., simultaneous saccharification and fermentation (SSF). In this research, the kinetic model parameters of the cellulose saccharification pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Several studies have shown that, for bioethanol production, the aeration strategy is as important as substrate feeding. Aeration is also believed to improve the overall productivity of the SSF process (22,23). These experimental results confirm that improving the aeration of PU carriers promotes rapid proliferation of fungi and increases saccharification enzyme production.…”
Section: Effect Of Z Mobilis Alginate Bead Size On Bioethanol Producsupporting
confidence: 71%
“…Several studies have shown that, for bioethanol production, the aeration strategy is as important as substrate feeding. Aeration is also believed to improve the overall productivity of the SSF process (22,23). These experimental results confirm that improving the aeration of PU carriers promotes rapid proliferation of fungi and increases saccharification enzyme production.…”
Section: Effect Of Z Mobilis Alginate Bead Size On Bioethanol Producsupporting
confidence: 71%
“…In the work by Ko et al (2010), rice straw was collected to convert cellulose into ethanol through enzymatic hydrolysis followed by fermentation. In their research, the kinetic model parameters of cellulose saccharification were determined from real experimental data for cellulase hydrolysis.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…Therefore, it is important to find new types of biomass for ethanol production. Lignocellulosic materials such as crop residues, grass straw, saw dust, and wood chips are particularly suitable sources due to their high abundance, low cost, and that their uses do not compete with food supply [1][2][3]. The development of ethanol production from these sources is thus considered as the second-generation biofuel technology.…”
Section: Introductionmentioning
confidence: 99%